The Two-Phase Hele-Shaw Problem with a Nonregular Initial Interface and Without Surface Tension - Bazaliy, B.V.; Vasylyeva, N. (Журнал математической физики, анализа, геометрии, 2014)
In the paper, we consider the two-dimensional Muskat problem without surface tension on a free boundary. The initial shape of the unknown interface has a corner point. We prove that the problem has a unique solution in the weighted Hölder classes locally in time and specify the sufficient conditions for the existence of the "waiting time" phenomenon. Изучается задача Маскета без учета поверхностного натяжения свободной границы. Неизвестная граница в начальный момент времени имеет угловую точку. Доказывается существование и единственность локального решения в весовых пространствах Гельдера, находятся достаточные условия на начальные данные, при которых существует феномен "времени ожидания".